2021
DOI: 10.1186/s12890-021-01481-y
|View full text |Cite
|
Sign up to set email alerts
|

The effect of atorvastatin on inflammatory markers in sulfur mustard gas induced bronchitis: a randomized double-blinded, placebo-control clinical trial

Abstract: Background This study was performed to evaluate the anti-inflammatory effect of atorvastatin in patients with chronic bronchitis, exposed to sulfur mustard gas. Methods In this randomized double-blinded clinical trial we recruited patients with chronic bronchitis after exposure to sulfur mustard gas. Ninety men 45–75 years old diagnosed with chronic bronchitis after exposure to mustard gas during the Iran-Iraq war, were randomly assigned to receiv… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…In addition, the serum procalcitonin levels in the 80/40-mg group were significantly lower than those in the other two groups at 3 days after PCI. For patients with bronchitis or pneumonia, low-dose atorvastatin treatment (20 mg or 40 mg) did not significantly change the procalcitonin level compared to placebo [34,35]. It is suggested that the early application of atorvastatin can inhibit the inflammatory response, high-dose of atorvastatin before PCI has a strong anti-inflammatory effect, and the anti-inflammatory effect of atorvastatin is dose-dependent.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the serum procalcitonin levels in the 80/40-mg group were significantly lower than those in the other two groups at 3 days after PCI. For patients with bronchitis or pneumonia, low-dose atorvastatin treatment (20 mg or 40 mg) did not significantly change the procalcitonin level compared to placebo [34,35]. It is suggested that the early application of atorvastatin can inhibit the inflammatory response, high-dose of atorvastatin before PCI has a strong anti-inflammatory effect, and the anti-inflammatory effect of atorvastatin is dose-dependent.…”
Section: Discussionmentioning
confidence: 99%